A comparative study of hyperbaric bupivacaine with fentanyl and sequential administration of isobaric and hyperbaric bupivacaine with fentanyl in caesarean delivery - Zinzuwadia, Praful J.; Patel, Dipika P.; Sheth, Paresh N.; Patel, Aneri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: To compare intrathecal sequential plain and hyperbaric Bupivacaine with fentanyl and hyperbaric Bupivacaine with fentanyl for hemodynamic stability, onset of block and duration of block in patients undergoing caesarean delivery under spinal anesthesia. Methods: This observational, double-blind study, seventy full term parturient, randomly divided to receive either 10 mg 0.5% Hyperbaric Bupivacaine with 25µg Fentanyl or 5 mg each of 0.5% plain and hyperbaric bupivacaine with 25 µg of Fentanyl. Surgery was allowed to proceed when block height reaches T6. Hemodynamic parameters, ephedrine use, time to reach peak dermatomal level and duration of sensory and motor block were compared among two groups. Results: Demographic data, quality of perioperative anesthesia, Apgar score were identical in both groups. Incidence of Hypotension in HB (77.14%) as compare to 25.71% in PHB. Nausea/Vomiting in both the groups, 68.57% for HB and 25.71% for PHB. For HB, 80% (10.3mg) of patients required Ephedrine while 17 % (4mg) in Group PHB. Peak dermatomal level in minutes was faster in HB (06±1.13) as compare to PHB. (9.06±0.76) Maximum Block level was achieved in HB was T4.94±0.76 and in PHB it was 5.71±0.86. Time to regression of sensory block in minutes for HB was 234.86±10.49 and PHB 258.14±12.37. Recovery from motor block is faster in HB (190.66±10.38) compared to PHB (205.71±11.95). Conclusions: Sequential administration of low dose of hyperbaric and plain bupivacaine with fentanyl provides better hemodynamic stability, accomplish adequate level of sensory and motor block in obstetric population for caesarean delivery.